Agogo Presbyterian College of Education Under the Missionaries and After Take-Over by the Government (1931-2013): A Comparative Study (International Journal of Scientific Research and Management (IJSRM), 2020)
The study analyzed the Agogo Presbyterian College of Education (1930-1971) and when it was taken over by the Government (1972-2013). This became relevant in the wake of the recent plea by the churches that the Government should hand over Mission Schools to the churches. The study therefore examines the state of management and leadership and infrastructural development both under the regime of the Missionaries and the Government. It also sought to assess academic standard of the students, and the discipline of the College, qualification of the teachers, supervision, and students’ patronage of library and entry grade of students to the College with the view of establishing the progression or retrogression over the period. In doing this, a comparative study was undertaken and data were derived from archival materials of the Agogo Presbyterian College of Education, and direct interviews with past Principals and Administrators of the College. The results revealed that despite an increase in student-intake (210 students in 1942 to 750 students in 2014) with a corresponding increase of teachers (from 5 missionary teachers with lower academic degrees in 1931 to 28 teachers with masters qualifications), inadequate infrastructural development; lack of discipline and competitions among students have characterized APCE since it was managed by the Government as compared to the Missionaries. The study recommends that the Government would complete the construction of the students‟ hall complex, and also put up large auditorium and classroom blocks to accommodate the high students’ intake in the College to enhance education delivery.